2011
DOI: 10.1093/infdis/jiq113
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Primes Mice for Pneumonia From Staphylococcus aureus

Abstract: Superinfections from Staphylococcus aureus following influenza are an increasing concern. We assessed several laboratory and clinical strains in a mouse coinfection model with influenza virus. A methicillin-resistant USA300 clone and several recent clinical strains from patients with necrotizing pneumonia caused high mortality following influenza virus infection in mice. Both viral and bacterial lung titers were enhanced during coinfections compared with single infections. However, differences in titers did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
142
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(160 citation statements)
references
References 46 publications
9
142
2
7
Order By: Relevance
“…In an animal study of co-infected mice, similar to the data reported by McCullers using co-infected mouse models [15][16][17], we observed pathological changes accompanied by pulmonary alveolar hemorrhage in addition to a significantly decreased survival rate [18]. Influenza virus or S. pneumoniae infection alone induced moderate pneumonia, whereas co-infected mice showed severe bronchopneumonia with massive hemorrhage, resulting in death of these mice two days after inoculation with S. pneumoniae.…”
Section: Related Molecules Referencessupporting
confidence: 87%
“…In an animal study of co-infected mice, similar to the data reported by McCullers using co-infected mouse models [15][16][17], we observed pathological changes accompanied by pulmonary alveolar hemorrhage in addition to a significantly decreased survival rate [18]. Influenza virus or S. pneumoniae infection alone induced moderate pneumonia, whereas co-infected mice showed severe bronchopneumonia with massive hemorrhage, resulting in death of these mice two days after inoculation with S. pneumoniae.…”
Section: Related Molecules Referencessupporting
confidence: 87%
“…Overall, the immunosuppressive effect of NS1 extend to the expression of multiple cytokines, likely contributing not only to impaired viral clearance, but also to impaired responses to unrelated pathogens (Fernandez-Sesma et al, 2006). Additionally, the genome of most influenza A isolates codes for the accessory protein PB1-F2, a cytotoxin that worsens the outcome of secondary bacterial infections with S. aureus and S. pneumoniae (Iverson et al, 2011;McAuley et al, 2007).…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Subsequent studies found that influenza infection predisposes an animal to a more severe pneumococcal infection [9]. The viral-bacterial interaction is not limited to influenza and S. pneumoniae: similar interactions have been noted between human metapneumovirus and S. pneumoniae [10] and between influenza and S. aureus [11][12][13].…”
mentioning
confidence: 86%